miR-9-1 gene methylation and DNMT3B (rs2424913) polymorphism may contribute to periodontitis - Marina Castro Coêlho; Ingrid Costa Queiroz; José Maria Chagas Viana Filho; Sabrina Garcia de Aquino; Darlene Camati Persuhn; Naila Francis Paulo de Oliveira (University of São Paulo, 2020)
Abstract Genetic and epigenetic changes have been associated with periodontitis in various genes; however, little is known about genes involved in epigenetic mechanisms and in oxidative stress. Objective: This study aims to investigate the association of polymorphisms C677T in MTHFR (rs1801133) and −149C→T in DNMT3B (rs2424913), as well as the methylation profiles of MTHFR, miR-9-1, miR-9-3, SOD1, and CAT with periodontitis. The association between polymorphisms and DNA methylation profiles was also analyzed. Methodology: The population studied was composed of 100 nonsmokers of both sexes, divided into healthy and periodontitis groups. Genomic DNA was extracted from the epithelial buccal cells, which were collected through a mouthwash. Polymorphism analysis was performed through polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP), while methylation-specific PCR (MSP) or combined bisulfite restriction analysis techniques were applied for methylation analysis. Results: For DNMT3B, the T allele and the TT genotype were detected more frequently in the periodontitis group, as well as the methylated profile on the miR-9-1 promoter region. There was also a tendency towards promoter region methylation on the CAT sequence of individuals with periodontal disease. Conclusion: The polymorphism −149C→T in DNMT3B (rs2424913) and the methylated profile of the miR-9-1 promoter region are associated with periodontitis.